EVALUACIÓN DE LA CALIDAD EN EL SERVICIO OFRECIDO POR LA COOPERATIVA DE AHORRO Y CRÉDITO EDUCADORES DE LOJA DESDE LA PERSPECTIVA DEL SOCIO A TRAVÉS DEL SERVPERF - ORDÓÑEZ GUALÁN, LIDA CATALINA (2019)
The overall objective of this research is to measure the quality in the service offered by the Savings and Credit Cooperative "Loja Educators" from the perspective of the partner through SERVPERF. For the realization of the same, the specific objectives were set out which are to determine the quality of service using the Servperf model considered as one of the most important models presented by Cronin & Taylor (1992-1994) which employs 22 assertions regarding the customer's perceptions of the service received based on 5 dimensions: tangible elements, refers to the appearance of physical facilities, equipment and employees; reliability, which is the organization's ability to deliver on what is promised and to do so without errors; responsiveness is the willingness to help users, the speed and agility of the service; Safety, describes knowledge, courtesy of employees, ability to inspire trust and security; empathy, refers to careful and individualized attention, the ability to listen and understand needs. Therefore, the first objective is to determine the influence of tangible elements on the quality of service of the Cooperative; the second objective is to establish the degree to which reliability influences quality of service; the third objective is to interpret at what level the responsiveness influences the quality of service; the fourth objective is to determine the influence that safety has on the quality of service and finally, to analyze the impact generated by the empathy dimension on the quality of the service of the Savings and Credit Cooperative "Educadores de Loja". In order to meet the objectives, the Servperf model measuring instrument was applied, in addition, socio-economic information questions were included as those that served to complement the research, the survey was conducted at the headquarters of the Cooperative to a random sample of 356 members and the information obtained was carried out for statistical analysis. Likewise, the methodology developed corresponds to a descriptive and quantitative study. From the survey result, it was determined that the Savings and Credit Cooperative "Educadores de Loja" obtained an overall average of perceptions of 4.36/5 indicating that the level of quality of service, based on a scale of 0 to 5 is high that in general they value the attention received as good and that the closer the five is close to reaching the perfect rating. 5 Spearman's coefficient is 0.848 which indicates that there is a very strong positive correlation between the dimensions of the SERVPERF model and the quality of service. The dimensions tangible elements and empathy are the most valued by the partners, while in the reliability dimension there is weakness, because the partners show that the Cooperative is not fully complying with the organization of the promised time for the realization of the service. It is important to note that the applied perception survey made it possible to know the effectiveness of the quality of service and Spearman's coefficient determined the degree of influence of dimensions.